Efektivitas Produk Afirmasi “Cheermail” Terhadap Peningkatan Iklim Kerja Positif Karyawan di PT. Baruga Asrinusa Development - Auralia M, Nurul; Fiqh, Salsabila; Tridinistari, Divka; Zainuddin, Kurniati (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The purpose of this study was to evaluate the effectiveness of the affirmation product "Cheermail" in enhancing a positive work climate, including emotional well-being, work motivation, interpersonal relationships, and appreciation culture at PT. Baruga Asrinusa Development. This experimental research utilized a pretest-posttest design. A total of 71 respondents from various departments completed a pretest before the implementation of Cheermail and a posttest after its implementation. Data were collected via Google Forms with the aid of QR codes and analyzed using SPSS 26 software, employing descriptive statistical analysis, correlation tests, and paired sample T-tests. The questionnaire respondents were predominantly millennials, comprising 70% of the sample, with the majority from the residential sales department at 25%. Female respondents made up 60% of the sample, while males constituted 40%. Pretest results showed a mean score of 24.58, while posttest results significantly increased to a mean score of 47.68. Statistical analysis revealed a mean increase of 22.189, with a standard deviation of 3.844 and a t-value of 50.634. The p-value (sig) of 0.991 < 0.05 indicated a significant relationship between the use of Cheermail and the improvement of a positive work climate among employees at PT. Baruga Asrinusa Development. This study demonstrates that Cheermail is effective in enhancing the overall positive work climate within the company, including strengthening the appreciation culture, fostering a more collaborative work environment, and triggering a positive domino effect. Future recommendations include integrating Cheermail into broader employee development programs and expanding its usage scope.